Mechanical properties of cold bonded quarry dust aggregate concrete subjected to elevated temperature. (30th October 2016) - Thomas, Job; Harilal, B.
Highlights: Quarry dust aggregate concrete (QDAC), a new alternate material for concrete is suggested. The effect of high temperature on the mechanical properties of QDAC is discussed. The exposure temperature is the most significant factor affecting the mechanical properties of cold bonded aggregate concrete. Abstract: The use of waste materials such as fly ash and quarry dust in the building construction process is explored in this paper. The coarse aggregate prepared using quarry dust and fly ash by cold bonding process is used for the making of concrete. The mechanical properties of the concrete, namely, compressive strength, splitting tensile strength and modulus of elasticity are determined. The variables considered are aggregate ratio, water binder ratio, temperature ratio and type of aggregate. For cold bonded aggregate concrete, it is found that the strength of the concrete is completely lost when exposed to certain limiting temperature. The limiting temperature is different for fly ash aggregate and quarry dust aggregate concrete. The limiting temperature of fly ash aggregate concrete is 300 °C and that of quarry dust aggregate concrete is 400 °C. This is due to the variation in the agglomeration process of fly ash and quarry dust in cold bonding process. The scanning electron microgram of spit aggregate on the cracked face of the specimen shows the evidences of formation and expansion of cavities due to the exposure to high temperature. The multiple regression models for the prediction of mechanical properties are developed. The present study gives an insight to the end users regarding the scope of the utilization of cold bonded aggregates in construction exposed to temperature.